Original paperA study of high-dose-rate intracavitary brachytherapy boost for curative treatment of uterine cervical cancer - Okuma, Kae; Yamashita, Hideomi; Kobayashi, Reiko; Nakagawa, Keiichi (Journal of Contemporary Brachytherapy, 2015)
Purpose : This study assessed the trial of boost intracavitary brachytherapy (ICBT) for the patients of uterine cervical cancer with residual malignant cells detected at the final stage of ICBT. Material and methods : This is a retrospective analysis of 75 patients with cervical cancer treated radically with external beam radiotherapy and high-dose-rate intracavitary brachytherapy between August 2004 and December 2008. Eighteen patients (24%) out of 75 received one additional ICBT and five patients (7%) had two additional ICBT. All 75 patients were retrospectively analyzed. The median follow-up time was 30 months. The median age was 59 years (range 28-85 years). There were 12 patients (16%) in stage IB, 27 (36%) stage II, 22 (29%) stage III, and 14 (19%) stage IV. Results : The 5-year overall survival rate was 65%. Non-hematological toxicities greater than grade 2 occurred in 12 patients (16%). Of these, only two patients received on additional ICBT. No significant difference was found in grade 3 toxicity between patients who did and did not receive additional ICBT (p = 0.8). Conclusions : The method to perform dose escalation should be examined depending on the treatment response.